Diversity of Aquatic Macrophytes with reference to Water Quality in Jakhor Lake, Dhangadi, Kailali (AMC Journal (Dhangadhi), 2025)
Water quality and other physical environmental factors determine the considerable variations in distribution and composition of aquatic species in freshwater ecosystems. Present study determined the physico-chemical parameters of water like temperature, pH, conductivity, nitrate, and ammonia which has brought variations in species community of macrophytes. Among all studied water parameter, Water temperature, ammonia, and conductivity are found to be most important influencing factor for macrophyte distribution while pH and nitrate have less influence. Altogether 37 Macrophyte species belonging to 21 families were recorded with the dominancy of emergent species, from the study area. Most of the macrophyte species showed strong but negative affinity with ammonia and water temperature. Jakhor Lake, which can be used for its management. This, study also provides useful information for decision makers aimed to the conservation and sustainable management of the lakes in Nepal.